Desenvolvimento de rotas de veiculação de microrganismos de uso agrícola - Alves, Bruna Lendzion (Universidade Federal de São Carlos, 2025)
Azospirillum brasilense, one of the most widely used species in inoculants worldwide, is a versatile rhizobacterium that enhances nitrogen availability and nutrient uptake, as well as promotes plant growth. Although the benefits of Azospirillum in agriculture are well established, its performance is often limited by the inadequacy of conventional formulations. Improving its field efficiency can be achieved through the development of formulations designed to provide robust protection against such challenges, such as those based on bacterial encapsulation in polymers. In this study, a novel powder formulation based on a poly(glycerol citrate) (PGCit) matrix, a biocompatible and sustainably synthesized polymer, was developed. The first stage consisted of standardizing a PGCit production methodology, aiming to establish synthesis conditions that optimize the balance between polymer yield and water solubility. Two molar ratios (equimolar and with excess citric acid) and reaction times ranging from 30 to 105 minutes were initially compared. Based on the structural and thermal characterization results, the material obtained under equimolar monomeric ratio and 75-minute synthesis time was selected. Formulations were produced by treating the polymer with calcium carbonate to adjust the pH and form powder. For drying the material containing trehalose and Azospirillum, three methods were tested (oven convection, freeze-drying, and spray-drying). Cell viability was assessed at time zero and up to 180 days of storage. Initially, regardless of the drying process, the formulations showed viability on the order of 10⁸ CFU/g, and the freeze-dried formulation maintained this level throughout the evaluation period, demonstrating excellent stability. Moreover, the freeze-dried formulation was tested in an Azospirillum recovery assay on maize seeds, showing superior performance compared to the liquid inoculant used as a control. In summary, the results demonstrate the protective role of the PGCit-based matrix, establishing it as a promising new carrier for seed-applied inoculants.
Development of formulation delivery routes for agricultural microorganisms
Keywords: Azospirillum brasilense; Encapsulamento; Poliglicerol citrato; Aplicação via semente; Azospirillum brasilense; Encapsulation; Poly(glycerol citrate); Seed application; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA; 2. Fome Zero e Agricultura Sustentável